Validation of the Everyday Technology Use Questionnaire in a Japanese context - Camilla Malinowsky; Anders Kottorp; Rumi Tanemura; Eric Asaba; Toru Nagao; Kazue Noda; Jiro Sagara; Peter Bontje; Lena Rosenberg; Louise Nygård (SAGE Publishing, 2015)
Background/Objective: The Everyday Technology Use Questionnaire (ETUQ), which evaluates the perceived relevance of and the perceived ability in everyday technology (ET) use, has demonstrated acceptable psychometric properties in Swedish studies of older adults. The aim of this study was to examine the reliability and validity of the ETUQ in a Japanese context in older Japanese adults. Methods: A sample of older Japanese adults (n = 164) including persons with (n = 32) and without (n = 132) cognitive impairment was interviewed with the ETUQ, including original items (ETs) and added Japanese context-specific items. Data were analyzed using a Rasch measurement model. Results: The analysis demonstrated acceptable functioning of the rating scale, internal scale validity, person response validity, and person-separation reliability of the Japanese ETUQ according to the Rasch model. However, evidence supporting unidimensionality in the Japanese ETUQ was not consistent in this sample. The added Japanese items did not significantly change the estimated individual person measures of perceived ability to use ET. Conclusion: The Japanese ETUQ seems to be a sensitive tool to evaluate perceived ability in ET use among elderly people in Japan with and without cognitive impairment. Therefore, it could be used in research and clinical practice.